Social equity and marine protected areas: Perceptions of small-scale fishermen in the Mediterranean Sea. (April 2020) - Bennett, Nathan J.; Calò, Antonio; Di Franco, Antonio; Niccolini, Federico; Marzo, Daniela; Domina, Ilenia; Dimitriadis, Charalampos; Sobrado, Francisco; Santoni, Marie-Catherine; Charbonnel, Eric; Trujillo, Maria; Garcia-Charton, Jose; et al.
Abstract: Global conservation policy requires the scaling up of effectively and equitably managed networks of marine protected areas (MPAs). While progress has been made on spatial coverage, the fundamental aspects of effectiveness and equity are falling short. Past research has focused on management effectiveness in MPAs, but less attention has been given to social equity though it is an ethical imperative and instrumental to conservation. This study assessed the perceptions of SSF regarding recognitional, procedural and distributional dimensions of social equity using quantitative surveys in 11 MPAs across 6 countries on the Mediterranean Sea. To do so, we developed individual indicators from which we created composite scores for recognitional, procedural, and distributional equity, and a combined social equity score. Overall, descriptive results showed that SSF perceptions of social equity were quite varied but slightly skewed towards positive perceptions. Then, we developed predictive models to analyze the effects of geographic (i.e., MPA and country) and individual (i.e., SSF demographics and characteristics) factors on the composite social equity scores. All social equity scores differed significantly between MPAs. Being an older fisher was associated with a decrease in recognitional equity, while having a higher level of relative wealth or more diversified livelihoods was associated with higher scores for distributional equity. These results point to the need for tailored management actions to improve equity in different MPA sites and for different groups. This paper presents a novel quantitative method for using stakeholder perceptions to examine social equity that might be applied to marine and terrestrial conservation initiatives elsewhere. Highlights: Global conservation policy requires the scaling up of effectively and equitably managed networks of MPAs. While progress has been made on spatial coverage of MPAs, effectiveness and equity are falling short. Social equity, which consists of recognitional, procedural and distributional dimensions, has received scant attention. This study examines perceptions of SSF regarding equity using surveys in 11 MPAs in the Mediterranean Sea. This paper presents a novel method for using stakeholder perceptions to examine social equity in conservation.